ANALISIS DAMPAK AKTIVITAS PASAR TERHADAP KINERJA RUAS JALAN RAYA PASAR KENTENG KULON PROGO MENGGUNAKAN PEDOMAN KAPASITAS JALAN (PKJI) 2023 - Widaryanto, Lilik Hendro; Hari Wibowo, M Fajar; Primadaru, Ridho (Department of Civil Engineering, Faculty of Engineer, Universitas Sarjanawiyata Tamansiswa, 2025)
Shopping services trade includes market activities. Activities involving people and vehicles have a positive impact on road and traffic management. Exchange is a market activity related to land use that has a significant impact on traffic development. This study aims to evaluate the performance of the Pasar Kenteng highway section to assess the quality of service provided on this section. The 2023 Road Capacity Guidelines (PKJI 2023) serve as the basis for this study. Primary and secondary data were used in the research. Primary data is obtained at the research location through direct observation. Secondary data is information gathered indirectly from primary sources, such as preserved historical records, notes, and reports. Microsoft Excel was used for calculations after obtaining these two data sets. On Monday, May 8, 2023, from 6:00 AM to 8:00 AM, side obstructions on the Pasar Kenteng highway section were categorized as